[Voxpopuli, Voxdel ; Magnificent obsession ; No pain, no vain - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Tackles reopening of Radio Veritas ; DZNN as commercial radio station ; Filipinos being obsessed with beauty contests; and aerobics as popular physical fitness exercises.
Voxpopuli, Voxdel (18 min.) -- Magnificent obsession (13 min.) -- No pain, no vain (10 min.).
VHS.
Keywords: Radio Veritas (Radio station : Quezon City).; DZNN (Radio station : Quezon City).; Radio stations -- Philippines -- Quezon City; Aerobic exercises; Physical fitness